2015
DOI: 10.1016/j.ymben.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of metabolic pathways to all traditional fermentation products increases ethanol yields in Clostridium thermocellum

Abstract: Clostridium thermocellum has the natural ability to convert cellulose to ethanol, making it a promising candidate for consolidated bioprocessing (CBP) of cellulosic biomass to biofuels. To further improve its CBP capabilities, a mutant strain of C. thermocellum was constructed (strain AG553; C. thermocellum Δhpt ΔhydG Δldh Δpfl Δpta-ack) to increase flux to ethanol by removing side product formation. Strain AG553 showed a two- to threefold increase in ethanol yield relative to the wild type on all substrates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 24 publications
1
55
0
1
Order By: Relevance
“…However, wild-type C. thermocellum is limited by its low ethanol yield and titer, producing acetate, lactate, H 2 , formate, free amino acids, and other compounds as additional fermentation products [2, 3]. Recent development of genetic tools for C. thermocellum [49] has enabled the construction of numerous targeted mutants, eliminating acetate, lactate, formate, and H 2 production [4, 7, 1014]. One of the mutations, C. thermocellum ΔhydG , eliminated a hydrogenase maturase protein involved in assembly of the [FeFe]-active site of three of the four hydrogenases in C. thermocellum .…”
Section: Introductionmentioning
confidence: 99%
“…However, wild-type C. thermocellum is limited by its low ethanol yield and titer, producing acetate, lactate, H 2 , formate, free amino acids, and other compounds as additional fermentation products [2, 3]. Recent development of genetic tools for C. thermocellum [49] has enabled the construction of numerous targeted mutants, eliminating acetate, lactate, formate, and H 2 production [4, 7, 1014]. One of the mutations, C. thermocellum ΔhydG , eliminated a hydrogenase maturase protein involved in assembly of the [FeFe]-active site of three of the four hydrogenases in C. thermocellum .…”
Section: Introductionmentioning
confidence: 99%
“…To date, the majority of C. thermocellum genetic engineering studies have focused on improving fuel production (24)(25)(26)(27)(28)(29)(30), but little genetic work has targeted understanding regulatory pathways. Here, we combine use of gene deletions with transcriptomics and DNA binding assays to gain insights into the regulatory networks of the three LacI transcription factors in the genome of C. thermocellum DSM1313.…”
mentioning
confidence: 99%
“…The same researchers added an artificial electron carrier (methyl viologen) which shifted the metabolic flux from acid to alcohol production, producing a high biofuel yield (0.39 g/g) from cellulose, comparable to ethanol yield from corn dextrose by yeast fermentation. A mutant strain of C. thermocellum, constructed to increase flux to ethanol by removing Yang et al,2015 side product formation, showed a two-to three-fold increase in ethanol yield relative to the wild type on all substrates tested (Papanek, Biswas, Rydzak, & Guss, 2015). A problem encountered with using lignocellulosic feedstock is the toxic compounds generated by its degradation which are inhibitory to clostridial growth.…”
Section: Genetic and Metabolic Engineering Approachesmentioning
confidence: 99%